Družinska fotografija kot eden od virov pri etnoloških raziskavah - Sosič, Barbara (Etnolog. Nova vrsta (Ljubljana), 2001)
The article presents the author's reflections on family photographs as a source in the research of different ethnological themes. If we manage to properly read the "message" contained in these photographs, we can establish that they witness to the way of living of people in the widest sense, that is to the role and place of a family's members within the family, to labour and the division of labour, fashion and costumes, values, individual elements of material culture, life stories, changes through time, etc. In order to treat a photograph as a source it is necessary to document all the data connected with it already upon its acquisition, as well as to understand the context in which it was taken. The photographic collection of the Slovene Ethnographic Museum has a considerable number of (mainly reproduced) family photographs which were mostly acquired in the course of researches into costumes and crafts. In the section dealing with the crafts the photographs related to individual families remained together and are linked with the other simultaneously acquired documentation and objects. This makes them an equally valid source for a variety of further researches. It has to be noted, however, that in spite of their specific way of accurately presenting reality, photographs, including family photographs, are not given the same treatment as other sources in ethnological research.
Keywords: fotografije; portreti; način življenja; raziskovalno delo; family; družina; ethnology; etnologija; viri